PENGARUH SAINTIFIK APPROACH TERHADAP 5M SISWA KELAS V PADA MATERI PANAS DAN PERPINDAHANNYA SDN KENCANA INDAH 1 KABUPATEN BANDUNG - Dwijayanti, Riska; Sujana, Atep; Subarjah, Herman (Jurnal Pena Ilmiah, 2019)
The scientific approach is learning that enhances 5M Ability (Observing, Asking, Collecting Information, Processing Information and Communicating). Therefore this study aims to determinee the ability of 5M studentts who learn through the Scientific approach before and after treatment in the experimental and controll classes. The research metho0d used7 was a quasi-experimentall design with nonequival9ent control groups. The study population was all fifth grade students of primary school throughout the Rancaekek District, Bandung Regency. Meanwhile, the study sample was SDN Kencana Indah 1. After studying for three meetings. The r8esults of the study can beseen from the calculation of the initial average score in the experimental class 10.5 to 17.2, and N-gain .72, the control class gets 10.2 to 13.6, and the N-gain value is , 36 Then it can be concluded that the Scientiific approach can improve the ability of 5M studen6ts compared to the Expository approach.